Wilson, et al., The Pursuit of Liberty - A history of the American People - Adomanis, James (Teaching History: A Journal of Methods, 1991)
Reviewing textbooks is like visiting the dentist for a checkup. The experience may be painful or it may be beneficial for you. Since Frances FitzGerald’s onslaught on the American textbook in the 1980s, publishers at the collegiate and pre-collegiate levels have been experimenting in order to upgrade and improve the backbone of classroom instruction, the textbook. Many publishers have heeded FitzGerald’s remarks about the dullness of textbooks by expending large sums of monies on the production of a grand design classroom teaching package.